Higher red blood cell distribution width at diagnose is a simple negative prognostic factor in chronic phase-chronic myeloid leukemia patients treated with tyrosine kinase inhibitors: A retrospective study. Issue 10 (12th March 2021) - Mao, Xia-Li; Xi, Ya-Ming; Li, Zi-Jian; Jia, Ming-Feng; Li, Ming; Wang, Li-Na; Zhao, Long; Zhang, Hao
Abstract : Abstract: The aim of this study was to evaluate the ability of the red blood cell distribution width (RDW) to predict prognosis and treatment response in chronic myeloid leukemia (CML)-chronic phase (CP) patients treated with tyrosine kinase inhibitor (TKIs). We retrospectively enrolled 93 newly diagnosed CML-CP patients treated with TKIs from 2009 to 2018 at the First Hospital of Lanzhou University. Patients were divided into 2 groups using an RDW of 18.65% determined by receiver operating characteristic curve analysis. We analyzed the correlation of treatment responses and the RDW compared to common scoring systems, as well as the correlation of the RDW with disease outcome, including overall survival (OS) and progression-free survival (PFS), and demographic and laboratory factors affecting outcome. Univariate analysis and Cox regression analysis were used. The median age of patients was 40 years, and 51 patients (54.8%) were men. A high RDW could predict treatment response at 3 months ( P = .03) and 6 months ( P = .02). The RDW was significantly lower in patients who achieved molecular response by 3 months ( P < .001) and complete cytogenetic response by 6 months ( P = .001) than in those who did not respond. Patients with a high RDW (>18.65%, n = 35) had significantly worse 5-year OS (77.1% vs 96.6%; P = .008) and PFS (80.0% vs 98.3%; P = .002) than those with a low RDW (⩽18.65%, n = 58). Multivariate analysis demonstrated that a high RDW was an adverse predictor of OS ( P = .005, HR (hazard ratio) = 9.741) and PFS ( P = .009, HR = 16.735). The RDW is a readily available prognostic marker of outcome in patients with CML-CP and can predict treatment response to TKIs. Further larger and prospective studies are required.